PRESUPPOSITION TRIGGERS OF ISRAELI-PALESTINIAN NEWS FOUND IN ONLINE AL-JAZEERA AND FOX NEWS - Abni Sintia Hasta; Leni Marlina (Universitas Negeri Padang, 2018)
Presupposition as property of language is used to build and influence audience’s opinion by the language users. In the news, presupposition triggers is a sign to trigger the use of presupposition. The purpose of this study is to analyze the use of presupposition triggers in Israeli-Palestinian news in the two online news; Al-Jazeera and Fox news. This research used the descriptive qualitative method. The data of this research is the Israeli-Palestinian news in two online Al-Jazeera and Fox news. The news that is analyzed are two news from Al-Jazeera and one news from Fox news. This data were analyzed based on Khaleel’s theory (2010) about presupposition triggers. The results of analysis showed that in Al-Jazeera, the highest occurrence is existential (definite description) that occurred 28 times (43%), and 20 times (40%) in Fox news. In addition both Al-Jazeera and Fox news used change of state verb in lexical, and adverbial clause in structural as the dominant types. In contrast, the difference on the two online news is the use of verb of judging.